Skojarzone chirurgiczno-farmakologiczne leczenie makulopatii cukrzycowej - Robaszkiewicz, Jacek; Chmielewska, Katarzyna; Figurska, Małgorzata; Frontczak-Baniewicz, Małgorzata; Stankiewicz, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
There are at least three avenues of investigation that support the theoretical value of vitrectomy for the treatment of DME, based on (1) vitrectomy with ILM peeling for the relief of traction on the macula, (2) vitrectomy to improve oxygenation of the macula leading to decreased vascular permeability with subsequent resolution or decrease in DME, and (3) ILM peeling to remove a part of the Müller cell endfeet and the horizontal gliosis. Visual improvement could be due to the induction of a higher overexpression of GFAP at the Müller cells level. It is likely that the proliferation of GFAP-stained gliofibrils, observed in these cells, preserves the blood-retinal barrier, reinforces architectural cohesion, and opposes the installation of the edema. In addition, the search for a specific pharmacological treatment is ongoing on the basis of new findings regarding the involvement of cytokines and growth factors in the formation of macular edema. Vascular endothelial growth factor (VEGF), inhibitors are currently being investigated in clinical studies. However, endogenous VEGF is required for visual function. Growing body evidence indicates that VEGF acts also on nonvascular cells, it plays survival role on Muller cells and photoreceptors. Therefore anti-VEGF therapies should be administered with caution.